Microstructure, Length, and Connection of Limbic Tracts in Normal Human Brain Development - Yu, Qiaowen; Peng, Yun; Mishra, Virendra; Ouyang, Austin; Li, Hang; Zhang, Hong; Chen, Min; Liu, Shuwei; Huang, Hao (Frontiers in Aging Neuroscience, 2014)
The cingulum and fornix play an important role in memory, attention, spatial orientation and feeling functions. Both microstructure and length of these limbic tracts can be affected by mental disorders such as Alzheimer’s disease, depression, autism, anxiety, and schizophrenia. To date, there has been little systematic characterization of their microstructure, length and functional connectivity in normally developing brains. In this study, diffusion tensor imaging (DTI) and resting state functional MRI (rs-fMRI) data from 65 normally developing right-handed subjects from birth to young adulthood was acquired. After cingulate gyrus part of the cingulum (cgc), hippocampal part of the cingulum (cgh) and fornix (fx) were traced with DTI tractography, absolute and normalized tract lengths and DTI-derived metrics including fractional anisotropy, mean, axial and radial diffusivity were measured for traced limbic tracts. Free water elimination (FWE) algorithm was adopted to improve accuracy of the measurements of DTI-derived metrics. The role of these limbic tracts in the functional network at birth and adulthood was explored. We found a logarithmic age-dependent trajectory for FWE-corrected DTI metric changes with fast increase of microstructural integrity from birth to 2-year-old followed by a slow increase to 25-year-old. Normalized tract length of cgc increases with age, while no significant relationship with age was found for normalized tract lengths of cgh and fx. Stronger microstructural integrity on the left side compared to that of right side was found. With integrated DTI and rs-fMRI, the key connectional role of cgc and cgh in the default mode network (DMN) was confirmed as early as birth. Systematic characterization of length and DTI metrics after FWE correction of limbic tracts offers insight into their morphological and microstructural developmental trajectories. These trajectories may serve as a normal reference for pediatric patients with mental disorders.